Coloring with Spiders: Our Favorites from Florida - L. A. Taylor; Samm Wehman Epstein (EDIS)
Florida has a rich diversity of spiders that vary greatly in body shape, size, color, hunting strategy, and habitat. While spiders are often feared, they are generally non-aggressive and provide essential ecosystem services, such as controlling pest insects in homes, gardens, and agricultural crops. This downloadable educational coloring book focused on spiders provides a creative way for people of all ages to appreciate the beauty and intrigue of spiders. It accompanies An introduction to Some Common and Charismatic Florida Spiders, a facts sheet highlighting some of the most commonly encountered spiders in Florida and some less common, but particularly charismatic, groups. The fact sheet, available at https://edis.ifas.ufl.edu/publication/IN1366, provides information on species biology along with images and descriptions for spiders across 15 families.